Chemical and physical behavior of natural and heat rectification wood oeucalyptus clones - Barreiros, Ricardo Marques [UNESP]; Lisboa, Felipe Dutra [UNESP]; Gouvea, Cantídio Fernando; Reis, Alessandra Maria Ferreira; Godinho, Emmanuel Zullo; Dias, Kelly Bossardi [UNESP] (Universidade Federal de Santa Maria, 2023)
Eucalyptus is a species of the most cultivated in the national scope, whose wood is widely used in the manufacture of furniture and other derived products. However, it is subjected to variations due to changes in moisture and other factors. To minimize such variations, some treatments were studied in a non-environmentally aggressive manner. This work analyzed the physical and chemical properties of wood of hybrid clones of Eucalyptus urograndis, “in natura” and thermally modified at temperatures of 140, 160, 180, 200 and 220°C, with 8.5 years of age, planted in Buri-SP, Brazil. The physical characterization was performed according to Brito, Garcia and Bortoletto (2006) and Brazilian Association of Technical Standards (1997), and the chemical characterization according to Technical Association of the Pulp and Paper Industry (1999). Through statistical analysis of factorial regression with significance of 5%, the clone factor did not cause interference in the analyzed properties; the variation that occurred was due to the temperature used; the hemicellulose was the main chemical property affected by the temperature; the most interesting treatments were those performed up to 180°C, since they did not compromise much the chemical properties of the wood and, consequently, would not affect so much their physical and mechanical properties.
Comportamento químico e físico da madeira natural e termorretificada de clones de eucalipto
Keywords: Basic density; Chemical composition; Heat rectification of wood; Wood quality